The Effect of Papaya Derived Exosome-like Nanoparticle as a Potential Photoprotective Agent in Nanocosmetics - Farid, Faticha Nasharo Qisthia; Barlian, Anggraini; Wibowo, Indra (HAYATI Journal of Biosciences, 2025)
Indonesia, as a tropical nation, experiences year-round ultraviolet radiation exposure. Excessive ultraviolet radiation, particularly UVB, accelerates premature skin aging, known as photoaging. UVB radiation induces photoaging by damaging DNA and increasing the production of reactive oxygen species (ROS), which leads to oxidative stress and results in increased apoptosis, melanogenesis, senescence, cell cycle arrest, and reduced cell migration capacity. Thus, identifying agents that can mitigate photoaging is crucial for developing skincare therapies. One of the alternative therapies currently being developed is plant-derived exosome-like nanoparticles (PDENs). Papaya (Carica papaya), renowned for its flavonoid and phenolic content, exhibits potent antioxidant properties and has been extensively utilized in skincare formulations. Therefore, this study investigates the effects of papaya-derived exosome-like nanoparticles (CP-PDEN) on inhibiting photoaging in 1BR3 fibroblast cell lines and zebrafish. Results indicated that CP-PDEN effectively internalized into 1BR3 cells and was categorized as nontoxic. The study then examined photoprotective effects after UVB irradiation (100 mJ/cm2) and found that CP-PDEN treatment resulted in better viability and nuclear morphology. Furthermore, CP-PDEN accelerates wound closure in 1BR3 cells and decreases melanocyte count in zebrafish compared with controls. In conclusion, CP-PDEN significantly enhanced cell viability and migration and suppressed melanogenesis, indicating its potential for anti-photoaging skincare applications.